1982
DOI: 10.3171/jns.1982.56.1.0158
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous migration of an intracranial bullet to the cervical spinal canal causing Lhermitte's sign

Abstract: A case is presented of a woman who was shot in the left occipital area with a .32 caliber automatic pistol. She was neurologically intact on admission, and skull x-ray films revealed the bullet in the right suboccipital area. On the 2nd day of the admission she developed Lhermitte's sign. Repeat films showed that the bullet had migrated to the C-4 vertebral level. The bullet was subsequently removed via a total laminectomy at C3-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…However, intracranial migration of bullets has been described in the literature [10, 11, 12, 13]and can occur in the intervening period between localization and surgical exploration [13]. In addition, the procedure is time-consuming and slightly more cumbersome.…”
Section: Discussionmentioning
confidence: 99%
“…However, intracranial migration of bullets has been described in the literature [10, 11, 12, 13]and can occur in the intervening period between localization and surgical exploration [13]. In addition, the procedure is time-consuming and slightly more cumbersome.…”
Section: Discussionmentioning
confidence: 99%
“…The time course for migration ranges from 2 days to 3 months. [2,7,10] The course of a ricochet bullet is different from migration movement of a retained bullet. A ricochet bullet changes its direction after hitting the wall of the cranium or spinal canal, whereas retained bullet migration may be affected by several factors, such as gravitational factors.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Gravitational force acting on the bullet, which is denser than the surrounding medium, has been suggested as a cause for migration caudally by the effect of gravity related to the position of the body, especially in the absence of significant cranial swelling. [7,10] Castillo-Rangel and Salvati [2,12] suggested that the ventricular system provides transport of the bullet from one area of the brain to another. Cerebrospinal fluid (CSF) flow and pulsation will facilitate the bullet's movement within the ventricle.…”
Section: Discussionmentioning
confidence: 99%
“…Migration of bullets can occur under four types of conditions 7) : Bullets in the ventricular system, or in the subarachnoid space, which are free to move 1,5,6,8) ; fragments in necrotic liquefied brain tissue, which move only to a limited extent in this cavity 2) ; projectiles in a trajectory of destructive brain tissue, which can move in the reverse direction; and the slow sinking of intact heavy bullets by gravity. 5,7,10) The third type must be unlikely, because brain swelling may collapse the bullet trajectory.…”
Section: Discussionmentioning
confidence: 99%